Early Flowering as a Drought Escape Mechanism in Plants: How Can It Aid Wheat Production? - Shavrukov, Yuri; Kurishbayev, Akhylbek; Jatayev, Satyvaldy; Shvidchenko, Vladimir; Zotova, Lyudmila; Koekemoer, Francois; de Groot, Stephan; Soole, Kathleen; Langridge, Peter (Frontiers in Plant Science, 2017)
Drought escape is a classical adaptive mechanism which involves rapid plant development to enable the completion of the full life-cycle prior to a coming drought event. This strategy is widely used in populations of native plants, and is also applicable to cereal crops such as wheat. Early flowering time and a shorter vegetative phase can be very important for wheat production in conditions of terminal drought since this can minimise exposure to dehydration during the sensitive flowering and post-anthesis grain filling periods. A gradual shift towards early flowering has been observed over the last century of wheat breeding in countries with a Mediterranean-type climate and frequent terminal drought. This trend is predicted to continue for wheat production in the coming years in response to global climate warming. The advantage of early flowering wheat is apparent under conditions of impending terminal drought. Under favourable conditions, a short vegetative phase can result in reduced plant biomass which will limit nutrients and assimilates for high grain yield in the absence of stress. However, where the early flowering trait exists in combination with other drought tolerance mechanisms and high yield potential have been reported, early flowering provides a promising strategy for the production of advanced drought-adapted wheat cultivars.